Inflammasome signaling is dispensable for ß-amyloid-induced neuropathology in preclinical models of Alzheimer’s disease - Srinivasan, Sahana; Kancheva, Daliya; De Ren, Sofie; Saito, Takashi; Jans, Maude; Boone, Fleur; Vandendriessche, Charysse; Paesmans, Ine; Maurin, Hervé; Vandenbroucke, Roosmarijn E.; Hoste, Esther; Voet, Sofie; et al. (Frontiers in Immunology, 2024)
Alzheimer's disease (AD) is the most common neurodegenerative disorder affecting memory and cognition. The disease is accompanied by an abnormal deposition of ß-amyloid plaques in the brain that contributes to neurodegeneration and is known to induce glial inflammation.Studies in the APP/PS1 mouse model of ß-amyloid-induced neuropathology have suggested a role for inflammasome activation in ß-amyloid-induced neuroinflammation and neuropathology. Here, we evaluated the in vivo role of microglia-selective and full body inflammasome signalling in several mouse models of ß-amyloid-induced AD neuropathology. Unexpectedly, microglia-specific deletion of the inflammasome regulator A20 and inflammasome effector protease caspase-1 in the App NL-G-F and APP/PS1 models failed to identify a prominent role for microglial inflammasome signalling in ß-amyloid-induced neuropathology. Moreover, global inflammasome inactivation through respectively full body deletion of caspases 1 and 11 in App NL-G-F mice and Nlrp3 deletion in APP/PS1 mice, also failed to modulate amyloid pathology and disease progression. In agreement, single-cell RNA sequencing did not reveal an important role for Nlrp3 signalling in driving microglial activation and the transition into disease-associated states, both during homeostasis and upon amyloid pathology. Collectively, these results question a generalizable role for inflammasome activation in pre-clinical amyloid-only models of neuroinflammation.